Granuloma Annulare - Leung, Alexander K.C.; Barankin, Benjamin; Hon, Kam Lun (International Journal of Pediatrics and Child Health, 2013)
Granuloma annulare is a benign, usually self-limited granulomatous disease of the dermis and subcutaneous tissue. Several distinct subtypes have been recognized, namely localized granuloma annulare, generalized or disseminated granuloma annulare, subcutaneous granuloma annulare, papular granuloma annulare, interstitial or patch granuloma annulare, and perforating granuloma annulare. Localized granuloma annulare is the most common form in children and comprises 75% of cases. Clinically, the condition is characterized by asymptomatic, flesh-colored or erythematous-brown papules, frequently arranged in a ring or annular pattern on the distal extremities. It is estimated that 0.1 to 0.4% of new patients attending dermatologic clinics have granuloma annulare. Most cases of granuloma annulare occur before the age of 30 years. A delayed hypersensitivity and cell-mediated immune response to an antigen contributes to the pathogenesis. Histologic examination of the lesion shows central collagen degeneration and mucin deposition surrounded peripherally by palisading histiocytes and inflammatory cells. Most cases of granuloma annulare are asymptomatic and self-limited; and reassurance is often sufficient. Treatment is mainly for cosmetic purposes and various modalities of treatment options are discussed.